A vaccination campaign in a Roma community in Rome: an experience of the Local Health Autority Roma1. (13th November 2019) - Spadea, A; Marino, M; Valentini, F; Furia, G; Frisicale, E M; Michelazzo, M B; Consoli, C; Forte, U; Bracci, S; Goletti, M
Abstract: Issue/problem: About 8, 000 Roma and Sinti live in the city of Rome, distributed in 33 settlements. This population is particularly at risk of health problems, due to social marginality and reduced access to health and social services. An important challenge for public health is therefore to guarantee and improve the right to health and the availability of health care. In Italy, a new vaccination law was approved in July 2017 and 10 vaccinations became mandatory for minors attending schools. Description of the problem: In 2018 the District 14 of the Local Health Authority Rome1 (LHA Rome1) organized a vaccination campaign for the Roma and Sinti community being in its area. The aim of the campaign was to analyse the vaccination status of children under-18 living in the camp, based on the local police census data, crossed with the web based regional vaccination registry, to offer free vaccination for those without a regular status, in order to allow school attendance. Results: Among 109 children living in the targeted Roma and Sinti camp, only 6 (5.5%) had a regular vaccination status according to the Italian law. Two different vaccination opportunity were offered to the community during 2018: a dedicated vaccination session in the local vaccination center, during which 6 children were vaccinated; four vaccination days offered directly at the Roma camp (a total of 53 children were vaccinated). At the end of 2018, the new Police census identified 114 minors resident in the camp instead of 109; of these, 48 (42.1%) had reached a regular vaccination status. Lessons: Addressing hard-to-reach communities in order to improve the access to health and social services is one of the LHA objectives. The intervention performed in the Roma camp was also an opportunity to promote the importance of vaccination and to inform the target community about various LHA services, in particular maternal and infant services, including those for Temporarily Present Foreigners. Key messages: The interventions performed straight into communities living in unfavorable health and social conditions are useful to improve the access to health and social services. Vaccination of people living in a social marginality is an important challenge for public health in order to guarantee specific protection measures and promoting the right to health.